Return Saham Pada Bank BUMN Yang Terdaftar di Bursa Efek Indonesia - Maria Yosepha Riwu; Ermalina Ermalina (Indonesian Journal of Economics Application (IJEA), 2021)
This study analyzes inflation, interest rates, and the rupiah exchange rate of stock returns on state-owned banks listed on the Indonesia stock exchange in 2012-2018. the research method used is a quantitative method with the type of associative research. The sample selection uses a purposive sampling method. The analytical method used is multiple linear regression analysis with SPSS version 22. based on the t-test results, the inflation variable has a significant effect on stock returns. The interest rate variable is having a substantial impact on stock returns. The variable rupiah exchange rate is having a considerable impact on stock returns. The f test results show that inflation, interest rates, and the rupiah exchange rate simultaneously significantly affect stock returns on state-owned banks listed on the Indonesia stock exchange in 2012-2018. The coefficient of determination results shows the adjusted r square value of 68%, which means the value of 68% stock returns is influenced by three independent variables: inflation, interest rates, and the rupiah's exchange rate.